Alternative methodological to favor the courteous motility in the children of the third year of life (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The joy to have a son is unique and brings once a great responsibility was matched up: Give it to educate it. It is necessary for the family, in addition to enjoy this so important event, to prepare to contribute to development herself and to the child's happiness. All little boy can grow and developing better if he is helped, if he is stimulated. The development of the courteous motility in the muscles of the hands, the face and feet constitutes an important link for the formation of the personality of the little boy. Present it investigation developed, for the sake of favoring the development of the courteous motility in the children of the 3er year of life, in the same they utilized methods and scientific techniques so much of the empiric level typical of the theoretician, that they enabled arriving at scientific conclusions, one there, manifest the scant bringing up to date of the educators of the Babyhood of the family in the development of the courteous motility in the children of the 3er and year of life. The obtained knowledge were been worth to elaborate an alternative that give answer to the detected problems. The same contains games and exercises conceived with a direct language, clearing and reachable. At the same time you favor the prominence of the family in the ample sense. The alternative as such constitutes a valuable material of consultation for investigators or another people gotten interested in the subject matter.
Keywords: courteous motility; family; education and community; physical exercise; educate your son